2012
DOI: 10.1063/1.4723718
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-induced modification of potassium-magnesium silicate glasses: An analysis of structural changes by near edge x-ray absorption spectroscopy

Abstract: The effects of femtosecond laser pulse irradiation on the glass structure of alkaline silicate glasses were investigated by x-ray absorption near edge structure spectroscopy using the beamline of the Physikalisch-Technische Bundesanstalt at the electron synchrotron BESSY II in Berlin (Germany) by analyzing the magnesium K-edge absorption peak for different laser fluences. The application of fluences above the material modification threshold (2.1 J/cm 2) leads to a characteristic shift of ∼1.0 eV in the K-edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Furthermore, in a recent paper, the technique of near-edge x-ray absorption spectroscopy was used by Seuthe et al for a detailed investigation of structural changes in potassium-magnesium silicate glasses following femtosecond-laser pulse irradiation [58]. A related, albeit more indirect, method for retrieving the local structure is Raman spectroscopy.…”
Section: Atomic-scale Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a recent paper, the technique of near-edge x-ray absorption spectroscopy was used by Seuthe et al for a detailed investigation of structural changes in potassium-magnesium silicate glasses following femtosecond-laser pulse irradiation [58]. A related, albeit more indirect, method for retrieving the local structure is Raman spectroscopy.…”
Section: Atomic-scale Structural Characterizationmentioning
confidence: 99%
“…The authors show that after single-pulse irradiation, a thin surface layer (∼50 nm) exhibits diffuse diffraction rings, indicating the formation of a layer of nanocrystalline diamond and possibly amorphous carbon. For potassium-magnesium-silicate glass, a recent x-ray absorption near-edge spectroscopy (XANES) study of laser-ablated regions has shown that above the ablation threshold, the magnesium K-edge undergoes a shift to lower energies, which is attributed to a reduced Mg-O bond length associated with a change in the average coordination number of the Mg ion from mainly sixfold coordinated to partly fourfold due to the irradiation [58]. This decrease in bond length, associated with densification, is similar to that observed by Raman spectroscopy of bulk modifications of BK7 when irradiated with MHz-repetition-rate, low-pulseenergy ultrashort pulses [60].…”
Section: 34mentioning
confidence: 99%
“…Several approaches have been employed to study fs-laser induced structural and/or chemical modifications. X-ray absorption near edge structure (XANES) spectroscopy has proven to be successful in estimating specific bond length variations in laser-irradiated potassium-magnesium silicate glasses 11 . Elemental mapping using energy dispersive X-ray analysis (EDX or EPMA) enabled the visualization of spatial ion migration in several glasses 12 13 .…”
mentioning
confidence: 99%
“…Phys. Lett In a recent paper, 1 Seuthe et al reported results on the structural changes due to femtosecond laser pulse irradiation in a glass with K 2 O-MgO-3SiO 2 composition (referred to as KMS3 from here on). The chosen technique, i.e., x-ray absorption near-edge structure (XANES) spectroscopy at the Mg K-edge, is well adapted to the study, and the interpretation of the XANES spectra is based on variations in the energy position of the first main peak, labeled A.…”
mentioning
confidence: 99%